Occlusive Thrombus Formation on Indwelling Catheters: In Vitro Investigation and Computational Analysis - Friedrich, Peter; Reininger, Armin J (Thrombosis and Haemostasis, 1995)
To determine the hydrodynamic parameters involved in thrombus formation on indwelling catheters, fibrin coagulation was investigated in an in vitro model and compared with the prevailing flow field. Computational analysis was used to simulate clot growth and identify the variables which determine its localization. The fibrin clot grew from the distal end of the catheter along the interface between the bulk stream and the annular vortex located immediately downstream of the catheter tip, finally filling the entire vortex. The calculations of flow parameters for three different growth stages showed that regions of clot formation always correlated with regions exhibiting the longest residence time. Fibrin clotting could be simulated by a mathematical model using residence time as the only variable parameter. Our results demonstrate that the residence time is the single most important flow factor for fibrin coagulation and thus probably for thrombus formation. When the residence time equals the clotting time for the fluid, thrombus formation is initiated. Conversely, it ceases when the area of long fluid residence times is replaced by a fibrin clot. Hence the fibrin clot represents a hydrodynamic optimization of the previously disturbed flow.